Long-Term Outcomes of Unprotected Left Main Percutaneous Coronary Intervention in Centers Without Onsite Cardiac Surgery - Hanson, L.; Vogrin, S.; Noaman, S.; Dinh, D.; Zheng, W.; Lefkovits, J.; Brennan, A.; Reid, Christopher; Stub, D.; Duffy, S.J.; Layland, J.; Freeman, M.; et al. (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2022)
Unprotected left main (LM) percutaneous coronary intervention (PCI) at centers without onsite cardiac surgery remains controversial. We aimed to evaluate the effect of onsite cardiac surgery on short-term and long-term outcomes in patients who had unprotected LM PCI. We analyzed Victorian Cardiac Outcomes Registry data on consecutive patients who had unprotected LM PCI at cardiac surgical centers (SCs) and non-SCs (NSCs) between January 2014 to December 2018. Compared with the SC group (n = 594, 81%), the NSC group (n = 136) were younger (69 vs 72 years) and presented with more ST-elevation myocardial infarction (35% vs 16%) and cardiogenic shock (25% vs 15%), with higher rates of preprocedural intubation (17% vs 11%) and mechanical circulatory support (20% vs 9.3%), all p <0.01. Unadjusted in-hospital mortality (23% vs 11.4%), and 30-day major adverse cardiac events (composite of mortality, myocardial infarction, stent thrombosis, or unplanned revascularization) (26% vs 16%) were higher in NSC patients, all p <0.01. However, following multivariable adjustment, SC was neither a predictor of in-hospital mortality (odds ratio 0.68, 95% confidence interval [CI] 0.32 to 1.43, p = 0.31), 30-day mortality (odds ratio 0.70, 95% CI 0.33 to 1.48, p = 0.35) nor long-term survival at 60 months (hazard ratio 0.88, 95% CI 0.62 to 1.27, p = 0.51). Propensity score analysis confirmed the neutral effect of onsite cardiac surgery on long-term survival (hazard ratio 0.99, 95% CI 0.66 to 1.50, p = 0.97). In conclusion, patients who underwent unprotected LM PCI at NSCs presented with greater acuity of illness. Despite this, the availability of onsite cardiac surgical support was not associated with in-hospital, 30-day, or long-term outcomes underscoring the safety of LM PCI in NSCs.